Suture-assisted punctoplasty - Sachdev, Amun (Digit J Ophthalmol, 2017)
PURPOSE: To describe a surgical technique in which a suture, instead of forceps, is used to improve access for the introduction of scissors and more easily achieve an appropriately-sized punctoplasty. MATERIALS AND METHODS: In this technique, a new modification of the 2-snip punctoplasty, a 6-0 polyglactin 910 suture is passed through the posterior wall of the punctum to apply traction. A video of the technique is provided. RESULTS: This technique improves the surgical field of view and eases access for introduction of Vannas scissors into the punctum to perform the punctoplasty. CONCLUSIONS: This simple and practical modification of the 2-snip punctoplasty improves instrument access so that an appropriately-sized punctoplasty can be performed with ease.